The European project on high temperature measurement solutions in industry (HiTeMS) – A summary of achievements. (January 2016) - Machin, G.; Anhalt, K.; Battuello, M.; Bourson, F.; Dekker, P.; Diril, A.; Edler, F.; Elliott, C.J.; Girard, F.; Greenen, A.; Kňazovická, L.; Lowe, D.; et al.
Abstract: High temperature measurement in industry is subject to large uncertainties due to the non-ideal measurement conditions; for example unknown emissivity and window transmission for radiation thermometry, sensor contamination and ageing causing unpredictable drift in contact thermometry. This paper gives an overview of a European Metrology Research Programme (EMRP) project "High Temperature Metrology for Industrial Applications" (HiTeMS) whose objective was to address, on a broad front, a number of unsolved measurement challenges in the domain of high temperatures (above 1000 °C) both in non-contact and contact thermometry. It brought together a total of 15 partner organisations; National Metrology Institutes (NMIs) (10), industrial companies (4) and a Fraunhofer Institute. The project started in September 2011 and was completed August 2014. Significant progress has been made in all the temperature measurement challenges tackled.